DESIGN PRINCIPLES AND BLOCK SCHEMES OF THE PROBE AUTOMATIC INSPECTION SYSTEMS FOR MICROAND NANOELECTRONICS ON A WAFER - V. A. Minchenko; G. F. Kovalchuk; S. B. Shkolyk (Приборы и методы измерений)
In this work we suggested the principles of design and block schemes of probe systems for analytical and interoperation measurement and inspection of high-speed microand nano on a chip systems in the nanosecond range. The sources of wideband signals distortion and errors of probe inspection systems for large integrated circuits inspection as well as transient response of high speed contacting probes are considered with the OTDR device with picosecond resolution. The features and defined errors of precision positioners for linear stepper motors and magnetic air motors for precise positioning of the probes on the pads with automatic sensing of LSI wafer are discussed.